MENGUATKAN ISLAM SEBAGAI MEDIA KRITIS ATAS “TEKS” BUDAYA POP - Ibnu Tyroz Aly (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
The present communication era led to a new phenomenon in the Islamic culture which is called as a mass or pop culture. The culture that tends to achieve high status, prestige, and pseudo honor through signs and symbols unfortunately results in a number of fundamental problems. This study will try to explore and examine on; how the Pop culture works; what is its correlation with Islam and what system can it be analyzed and approached. In an attempt to examine this phenomenon, the writer used Roland Bartens Semiotics approach that seeks to interpret every evolving evidences to be translated into a more dynamic model. In general, Islam is expressed through signs and then manifested into texts, this includes either contextual or textual text. Therefore, for its development, Islamic discourses should give a lot of attention to the contextual texts dimension of life in society, particularly those texts that relate to the contemporary life.